Selective Bifunctional Catalytic Conversion of Cellulose over Reshaped Ni Particles at the Tip of Carbon Nanofibers - Van de Vyver, Stijn; Geboers, Jan; Dusselier, Michiel; Schepers, Hans; Vosch, Tom; Zhang, Liang; Van Tendeloo, Gustaaf; Jacobs, Pierre A.; Sels, Bert F. (ChemSusChem, 2010)
Access to cellulose: Carbon nanofibers grown over Ni supported on γ‐Al2O3 act as efficient catalysts for the one‐pot conversion of cellulose to sugar alcohols, owing to the enhanced accessibility of the water‐insoluble substrate towards the active catalytic sites. The new catalyst design concept yields unprecedented results for selective cellulose conversion using inexpensive Ni catalysts.